CALCULATION OF HUMAN FATIGUE IN THE ENVIRONMENT OF LINGUISTIC VARIABLES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
In order to reduce the number of accidents in such sectors of work, such as, driving vehicles, the operator's work on the radar screen, a system is required capable of determining the degree of fatigue of a particular person at a given moment of time according to the data received from sources of information, preventing arbitrary fall asleep and providing recommendations for further action regarding rest options up to work suspension. The system shall be suitable for a situation where the space of the measured parameters consists predominantly of parameters with no numerical values (gradations). There is only a linguistic description with a scoring scale. For this parameter group, it is proposed to use the theories of the non-strict and linguistic variables for the implementation of decision procedures. It not only brings a portion of the system’s operating algorithm calculations into an environment of non-strict mathematics and also allows the decision to return to the normal environment. The work provides a calculation algorithm in a non-strict environment and a description of the resulting computer system.